2014
DOI: 10.1590/0001-3765201420130316
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Parkia pendula seed gum as matrix for Concanavalin A lectin immobilization and its application in affinity purification

Abstract: The present work aimed to magnetize Parkia pendula seeds gum and use it as a matrix for Concanavalin A covalent immobilization. This composite was applied in affinity purification of glycoconjugates. Parkia pendula seeds were hydrated and the gum provenient from the supernatant was precipitated and washed with ethanol and dried. The gum was magnetized in co-precipitation using solutions of Fe +2 and Fe +3 . Matrix activation was accomplished with NaIO 4 . Magnetized Parkia pendula seeds gum with covalently imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Rêgo et al [20] have reported a gum magnetic from Parkia pendula seeds as a matrix for concanavalin A (Con A) covalent immobilization. For this to be possible, seed gum was included in the solution containing the Fe 3+ and Fe 2+ ions.…”
Section: Synthesis Of Iron Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rêgo et al [20] have reported a gum magnetic from Parkia pendula seeds as a matrix for concanavalin A (Con A) covalent immobilization. For this to be possible, seed gum was included in the solution containing the Fe 3+ and Fe 2+ ions.…”
Section: Synthesis Of Iron Oxidesmentioning
confidence: 99%
“…The authors advice reading the review article to find more information about magnetic enzyme microreactors [46]. Biocompatibility, specificity, ability to recognize other molecules, and operational stability presented by biomolecules such as enzymes [2], carbohydrates [21], antibodies [47], antigens [48], peptides [49], DNA [50], and glycoprotein [20], among others, are properties that make biomolecules attractive to biotechnological applications. The possibility of reuse, the easy removal of the magnetic bio-derivative from the reaction medium, the greater stability of the biomolecule, the high productivity, and the low-cost of production are some of the advantages of the immobilization.…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomolecules have been separated using several techniques based on the interaction of specific molecules. Among these molecules of lectin-carbohydrate interactions are widely studied, from basic to applied natural and clinical sciences [3]. Lectins are used not only as molecular unifying to immobilize proteins but also used as the recognition element of biosensors, because of binding carbohydrate chains with high selectivity [2].Concanavalin A (Con A) from Canavalia ensiformis, a type of bean is a protein that is extracted.…”
Section: Introductionmentioning
confidence: 99%
“…Concanavalin A (Con A) is also a metalloprotein containing Mn 2+ and Ca 2+ [16]. Concanavalin A (Con A) has been extensively used in the isolation, fractioning and structural characterization of glycoproteins and other important glycoconjugates carrier glucose and/or mannose residues [3][4][5]. Each monomer contains an independent carbohydrate binding site, for glucose and mannose.…”
Section: Introductionmentioning
confidence: 99%